À l’intérieur de Seinfeld : la sitcom Jerry - Eric Gatefin (TV Series, 2014)
The principal narrative arc of the season 4 of Seinfeld, broadcasted on NBC, consists of a mise en abyme of the creation of the show. As it happens, this season fits into a more global transgressive process. The writing of Seinfeld is effectively founded upon an uncompromising denunciation of social conventions, moral dogmas, but also televisual codes related to sitcoms. This denunciation takes effect in the form of a charge. To show what, as a rule, escapes from view seems to be the goal of the screenwriters who, in their initiative to demystify taboos, include the mechanisms of production of the sitcom Seinfeld. The steps of the show’s creation presented in season 4 are the object of a corrosive treatment. From the fundamental absence of ideas among the supposedly creative characters to questionable pitches, passing by a far from brilliant financial negotiation, the show advances with difficulty toward its creation. Beyond the jolts that lead from the meeting with NBC to the broadcasting of an episode, the provocative character of the mise en abyme comes principally from the concept proudly sported by the character George: “a show about nothing”, a concept that puts the critical and demystifying approach of the show in the forefront. Far from figuring screenwriting cleverness, the narrative arc recounting the creation of the show exhibits, on the contrary, a will to deconstruct at work throughout the show. It enters as well into a game of echoes within a sitcom that makes self-reference its principal mode of function. In this way, the steps that lead to the production of the pilot articulate themselves with the sexual questions dealt with in several episodes: virginity, masturbation, frustration, homosexuality, and impotence. Directly or indirectly, creation and the characters’ sexual impulses interfere and shed light on one another.